Trying Territory: Missionaries and the Nexus of Local Power in Northwestern China (1923–1936) - CHEN, Yanrong (Journal of Research for Christianity in China (JRCC), 2025)
During the period of 1923–1936, three CIM female missionaries (Mildred Cable, Evangeline Frances French and Francesca Law French, also known as “the Trio”) itinerated along Gansu–Xinjiang Road (also Silk Road in China) and started a mission station in Suzhou. The evangelistic journeys led to their encounters and dialogues with local people, about which plenty of records have been written and kept till now. Specifically, all of these diaries, letters, articles, autobiographies and other books are the main part of primary material used in this research. The rest covers data from local society, involving archives and local documents, and collection of other contemporary travelers’ notes. Based on those materials in which many figures and events are present, the power structure in the local society, in which the missionaries settled themselves, can be discussed. This research takes the local perspective from below. It indicates that the power of the military dominated villages and small towns within this area; and between the military and grassroots people were local officials, gentry, merchant and religious leaders, who were supposed to play the role of guardians in rural society, but actually did not. By telling stories of the relationship between the missionaries and other figures, this paper is to trace how the three female missionaries and their community were finding a potentially appropriate approach to explore more space within the nexus of local power.